PERENCANAAN ARSITEKTUR ENTERPRISE SISTEM INFORMASI MENGGUNAKAN TOGAF DI SMA BPK PENABUR HOLIS - Danang Ardya Christianto; Jajat Sudrajat (STMIK Mardira Indonesia, Bandung, 2021)
BPK PENABUR HOLIS high school is a private school located in the city of Bandung. BPK PENABUR HOLIS senior high school is engaged in education. Information Systems and Information Technology is a basic requirement and has been applied in schools, but not all parts of implementing information systems as a result of data and information needs are not integrated, so that business process activities are not running effectively. To overcome this, by planning an enterprise architecture that can integrate existing systems with systems that will be built. This methodology uses the TOGAF ADM (Architecture Development Method) in collecting data using qualitative methods based on a description of the actual conditions by means of Literature Studies and interviews. The results of this study are the proposed blueprint of information systems and information technology that are needed now and in the future for business activity strategies at BPK PENABUR HOLIS high schools. Keyword: Architecture Enterprise, High School BPK PENABUR HOLIS, TOGAF ADM Framework.DOI : http://doi.org/10.5281/zenodo.4958211